Інтегрована гарантоздатна система управління вогнем і навігації самохідних ракетних та артилерійських систем на колісному та гусеничному шасі - Оліярник, Б. О.; Євтушенко, К. С.; Бондарук, А. Б.; Глєбов, В. В.; Казаков, Б. М.; Кононенко, В. О. (НТУ "ХПІ", 2009)
In this article structure of unified dependable integrated fire control and navigation system of selfpropelled rocket and artillery systems is discussed. System hardware, principles of operation, mathematical support, navigational information complexation algorithm are examined. Dependability procurement solutions are considered. The system is integrated into existing or next-generation automated fire control system of rocket, artillery or combined-arms unit.
Keywords: бойова машина; ракетна система; артилерійська система; управління вогнем; система навігації; математичне забезпечення